Dietary Oleocanthal Supplementation Prevents Inflammation and Oxidative Stress in Collagen-Induced Arthritis in Mice - Tatiana Montoya; Marina Sánchez-Hidalgo; María Luisa Castejón; María Ángeles Rosillo; Alejandro González-Benjumea; Catalina Alarcón- (MDPI AG, 2021)
Oleocanthal (OLE), a characteristic and exclusive secoiridoid of Oleoaceae family, is mainly found in extra virgin olive oil (EVOO). Previous studies have reported its antioxidant, anti-inflammatory, antimicrobial, anticancer and neuroprotective effects. Since the pathogenesis of rheumatoid arthritis (RA) involves inflammatory and oxidative components, this study was designed to evaluate the preventive role of dietary OLE-supplemented effects in collagen-induced arthritis (CIA) murine model. Animals were fed with a preventive OLE-enriched dietary during 6 weeks previous to CIA induction and until the end of experiment time. At day 43 after first immunization, mice were sacrificed: blood was recollected and paws were histological and biochemically processed. Dietary OLE prevented bone, joint and cartilage rheumatic affections induced by collagen. Levels of circulatory matrix metalloproteinase (MMP)-3 and pro-inflammatory cytokines (IL-6, IL-1β, TNF-α, IL-17, IFN-γ) were significantly decreased in secoiridoid fed animals. Besides, dietary OLE was able to diminish COX-2, mPGES-1 and iNOS protein expressions and, also, PGE2 levels. The mechanisms underlying these protective effects could be related to Nrf-2/HO-1 axis activation and the inhibition of relevant signaling pathways including JAK-STAT, MAPKs and NF-κB, thus controlling the production of inflammatory and oxidative mediators. Overall, our results exhibit preliminary evidences about OLE, as a novel dietary tool for the prevention of autoimmune and inflammatory disorders, such as RA.